2015
DOI: 10.1126/scitranslmed.aaa9223
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with autoimmunity drive NFκB signaling and responses to inflammatory stimuli

Abstract: The transcription factor NFκB is a central regulator of inflammation and genome-wide association studies in subjects with autoimmune disease have identified a number of variants within the NFκB signaling cascade. In addition, causal variant fine-mapping has demonstrated that autoimmune disease susceptibility variants for multiple sclerosis (MS) and ulcerative colitis are strongly enriched within binding sites for NFkB. Here, we report that MS-associated variants proximal to NFκB1 and in an intron of TNFRSF1A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 52 publications
6
82
0
Order By: Relevance
“…We recently found that MS-associated variants proximal to NFKB1 (rs228614) and in TNFRSF1A (TNFR1, rs1800693) are associated with increased NF-κB signaling after TNF-α stimulation (70). Both variants result in increased degradation of IκBα, a negative regulator of NF-κB and nuclear translocation of p65 NF-κB.…”
Section: Functional Interpretation Of Noncoding Variantsmentioning
confidence: 99%
“…We recently found that MS-associated variants proximal to NFKB1 (rs228614) and in TNFRSF1A (TNFR1, rs1800693) are associated with increased NF-κB signaling after TNF-α stimulation (70). Both variants result in increased degradation of IκBα, a negative regulator of NF-κB and nuclear translocation of p65 NF-κB.…”
Section: Functional Interpretation Of Noncoding Variantsmentioning
confidence: 99%
“…This transcriptional change results in an exaggerated cytokine production response from monocytes after stimulation with TNFα, and exacerbates inflammatory responses. As well as with the genetic variant affecting (or associated with) NF-κB, the study by Housley and coworkers demonstrates that the likely causal impact of rs1800693 variations in inflammation and response to TNFα involves increased activation of the NF-κB pathway (18). Current authors' findings suggest that altered TNFα induced NF-κB signaling was due to rs1800693 SNP exerting regulatory effects through changes in TNFR1.…”
Section: Genetic Variations Affecting Tnfr1 In Msmentioning
confidence: 65%
“…Firstly, these authors validated that naïve CD4 T cells from patients with MS exhibit increased IκBα degradation and higher phospho-p65 and NF-κB activation than age-matched healthy controls, and that this increased activation is mitigated by treatments affecting NF-κB (18). Then, they investigated whether stimulated circulating immune cells from subjects with different genotypes at rs228614 (AG; average heterozygosis ± standard deviation =0.5±0.008) resulted in greater degradation of IκBα and phosphorylation of p65 NF-κB in naïve CD4 T cells with the risk genotype (GG).…”
Section: Genetic Variations Affecting Nf-κb In Msmentioning
confidence: 99%
See 2 more Smart Citations